2018
DOI: 10.5194/hess-2018-264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vegetation vulnerability to drought on southeastern Europe

Abstract: Abstract. In this work, the impacts of drought events on vegetation activity in the period 1998-2014 were analysed, on an area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Shi et al (2021) reported that in arid and semi-arid regions, these correlation mainly was observed in short time scales, which as Namak Lake basin is mostly dominated by arid and semi-arid climate, the results obtained in the present study are consistent with their results. Also, (Páscoa et al 2018;Zhang et al 2017) reported that since the plants have shallow-rooted in the rainfed agricultural lands, their water demand is mainly dependent on surface soil water content. On the other hand, in forests and shrublands, where there is permanent vegetation cover, the plants have deeper roots and can use moisture from deep soil water content or groundwater in long term.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (2021) reported that in arid and semi-arid regions, these correlation mainly was observed in short time scales, which as Namak Lake basin is mostly dominated by arid and semi-arid climate, the results obtained in the present study are consistent with their results. Also, (Páscoa et al 2018;Zhang et al 2017) reported that since the plants have shallow-rooted in the rainfed agricultural lands, their water demand is mainly dependent on surface soil water content. On the other hand, in forests and shrublands, where there is permanent vegetation cover, the plants have deeper roots and can use moisture from deep soil water content or groundwater in long term.…”
Section: Discussionmentioning
confidence: 99%
“…The climate in the high altitude area changes with the increase of altitude, the radiation increases, and the temperature and precipitation decreased gradually. Due to the high sensitivity of grass to climate change, the growth of western alpine grass was limited (Nemani et al, 2003;Páscoa et al, 2018;Gao et al, 2019), thus shrinking the grass area in the western YRB (Table 2). With the gradual decrease of altitude, temperature and precipitation gradually increased as controlling factors influencing vegetation growth, and the change rate of temperature and precipitation would also gradually increase Frontiers in Earth Science frontiersin.org (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the monthly NDVIs, relatively more important appear those characterizing April and May, when vegetation activity, lower in the winter months, signifi cantly increases (Páscoa et al, 2018).…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%